Kajian mengenai pengetahuan dan sikap terhadap aids dan faktor-faktor yang mempengaruhinya ke atas penduduk batu 23, Sungai Nibong, Sabak Bernam pada bulan Oktober 1995 - Wan Mohd. Razin,; W.H.,; Abdul Hamid ,; J.Sharudin,; Zainal Effendy,; M.H.,; Mohd Razip,; S.Mohd Ali,; T. Junaidi,; Z.A.,; Azhar,; M.Mansor, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 1997)
A cross-sectional study was done in Kampung Batu 23, Sungai Nibong, Sabak Bernam on October 1995 to study the knowledge and attitude of the people towards AIDS and factors that influence them. A total of 197 respondents were selected randomly, which represented the target group population from the age 15 to 64. Data was acquired through guided-interview questionaire. The total respondence represents 31% of the total target group population. This study shows a significant relationship between the knowledge of AIDS with age, sex, the highest level of the formal education, the monthly income percapita and also the total duration of exposure to mass media. It also shows moderate correlation between the knowledge of AIDS with the attitude towards AIDS (r=0.56) and between the knowledge of general health with the knowledge of AIDS (r=0.40).